Blood and Fire : La Violencia in Antioquia, Colombia, 1946-1953 - Roldán, Mary, 1959- (Book collections on Project MUSE., 2002)
This study of one of the most deadly conflicts this hemisphere has ever experienced, the Colombian Violencia (1945-1958), demonstrates links between past and present violence and its connection to political democracy, racism, regionalism, and state format.